Investigation at the molecular level for a nifgenes to bacteria klebsiella pneumoniea the use of polymerase chain reaction (PCR) - Fawz Abdul Salam K.AL-Saffar; Abdul Razak K. Mahmood; Najwa I. AL- Barhawi (Tikrit Journal of Pure Science, 2023)
This research was aimed at detection on three nitrogen fixation genes nifK , nifD , nifH in 21 K. pneumonia pathogenic isolates which obtained from Prof. Jean-Marc in Leicester British  university by using PCR technique and four specific primers P1, P2 , P5 , P6 and compare it with K. pneumoniae 342 standard strain. The results showed presence of two bands for each isolate with M.W 0.5 Kbp  comparing  with 1 Kbp of the marker.